2020
DOI: 10.1103/physrevc.101.014611
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the one-neutron transfer in C13+Si28 at Elab<

Abstract: Background: Neutron transfer measurements for the 18 O + 28 Si system have shown that the experimental one-neutron and two-neutron transfer cross sections are well reproduced with spectroscopic amplitudes from two different shell model interactions for the Si isotopes: psdmod for the two-neutron transfer, and psdmwkpn for the one-neutron transfer.Purpose: The origin of this ambiguity can be related to a more complex mechanism in the one-neutron transfer that requires the unpairing of neutrons prior to its tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
3
2
0
Order By: Relevance
“…The total reaction cross sections for the reaction of induced on were predicted using the global OMPs of and . Compared with the existing experimental data from [11,12], the theoretical results are both in good agreement with the data from Ref. [12] and smaller than the data from Ref.…”
Section: Sisupporting
confidence: 69%
See 2 more Smart Citations
“…The total reaction cross sections for the reaction of induced on were predicted using the global OMPs of and . Compared with the existing experimental data from [11,12], the theoretical results are both in good agreement with the data from Ref. [12] and smaller than the data from Ref.…”
Section: Sisupporting
confidence: 69%
“…Compared with the existing experimental data from [11,12], the theoretical results are both in good agreement with the data from Ref. [12] and smaller than the data from Ref. [11].…”
Section: Sisupporting
confidence: 68%
See 1 more Smart Citation
“…This interaction was adopted in several of our previous studies, for instance in Refs. [35,37,60,[66][67][68], to calculate one-and two-nucleon spectroscopic amplitudes and was tested by comparing experimental and theoretical excitation energies of the projectiles and ejectiles involved in the studied reactions [60,67,68]. In particular, in Refs.…”
Section: One-nucleon Transfer Reaction Calculationsmentioning
confidence: 99%
“…In addition, with the unprecedented growth in computing power detailed nuclear structure calculations like large scale shellmodel ones are increasingly adopted for the determination of spectroscopic factors. Into this context, it has been demonstrated that it is possible to obtain reliable spectroscopic information from heavy-ion transfer reactions without the need for any arbitrary scaling factor [48][49][50][51][52][53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%